Pelatihan Pemanfaatan Smartphone Android Sebagai Media Pembelajaran Bagi Orang Tua Kelurahan Sidokerto Kecamatan Bumi Ratu Nuban - Mariana, Erni; Novita, Novita; Wardany, Kusuma; Sari, Reni Permata (UKInstitute, 2021)
This community service program has the following objectives, namely, 1) To introduce the use of an Android Smartphone with the Android application in the process of teaching and learning activities in class for parents/guardians of Sidokerto Village, Bumi Ratu Nuban District, Bumi Ratu Nuban District, 2) To increase the use of Android smartphones with the Android application for Parents / Guardians of Sidokerto Urban Village, Bumi Ratu Nuban District. The results of this dedication show that there is high enthusiasm from the participants during the delivery of the material and practices that are carried out. Apart from being active in providing responses and asking the participants, it also shows that the presentation given has been directly practised in the process of teaching and learning activities that they carry out. In this case, the participants feel they have had new experiences in the teaching and learning process, so the hope is that it can foster enthusiasm for learning and student creativity so that it can improve student achievement. Abstrak: Program pengabdian pada masyarakat ini memiliki tujuan yaitu, 1) Untuk mengenalkan pemanfaatan Smartphone android dengan aplikasi andorid dalam proses kegiatan belajar mengajar di kelas pada Orang Tua/Wali Murid Kelurahan Sidokerto Kecamatan Bumi Ratu Nuban, 2) Untuk peningkatan penggunaan pemanfaatan Smartphone android dengan aplikasi andorid bagi Orang Tua/Wali Murid Kelurahan Sidokerto Kecamatan Bumi Ratu Nuban. Hasil dari pengabdian ini menunjukkan bahwa adanya antusias yang tinggi dari peserta, selama penyampaian materi dan praktik yang dilakukan. Selain aktif memberikan tanggapan dan bertanya para peserta juga menunjukkan bahwa pemaparan yang disampaikan sudah dipraktikkan secara langsung dalam proses kegiatan belajar-mengajar yang mereka lakukan. Dalam hal ini peserta merasa mendapat pengalaman baru dalam proses belajar-mengajar, maka harapannya dapat menumbuhkan semangat belajar dan kreativitas siswa sehingga dapat meningkatkan prestasi siswa.